Multi-item inventory control with joint set-up cost - Vardar, Belkin (İlhan). (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1981., 1981)
In this study, a multi-item inventory control system fora firm where groups of items are supplied by their own specific factories, was developed. The dependence between items is caused by the set-up cost structure: When several items are ordered on the same order list, a fixed set-up cost, independent of-the number of items and quantities, is incurred. In order to use this fixed part of the ordering cost, a joint ordering policy, the (s,c,S), was recommended for the inventory system. As stated by this policy, ordering decisions are taken also for items with inventories -below, their can-order points (ci 'S) when any item with an inventory below its must-order point s is ordered. A model with a monetary objective function minimizing the sum of ordering and inventory carrying costs and satisfying service level constraints, was set-up. An optimization algori thm, which is, a combination of mathematical optimization and simulation was used to ,determine optimal inventory control parameters (must order points, can-order points, and order-up-to levels). The solution algorithm was programmed and, its implementation for a selected group of items was presented in the study. The cost saving achieved by the dependent policy over a usual, independent inventory control system was also; demonstrated. Finally, the algorithm's performance under changes in the uncontrollable system parameters was analyzed and a case where changes occur indemand figures was presented at the end of the study.
Keywords: Inventory control.